The evolving panorama of vascular access in the 21st century - Neyra, Nilda Roxana; Wazir, Shoaib (Frontiers in Nephrology, 2022)
There are three major types of hemodialysis vascular access: hemodialysis catheters, arteriovenous grafts, and arteriovenous fistulas. Arteriovenous fistulas provide the best access due to their reliability and long-term patency. They are recommended by the current Kidney Disease Outcomes Quality Initiatives (K-DOQI) guidelines; however, not all patients benefit from arteriovenous fistulas due to poor maturation or a lack of adequate vasculature. Currently, hemodialysis is initiated via catheters in the majority of patients. Catheters are associated with high morbidity and mortality due to infection, lower quality of dialysis, and the development of central vein stenosis. The varied responses of patients to the different access types exemplify the need to choose the “right access for the right patient” based on scores that can predict death risk and progression of chronic kidney disease. Additionally, vascular access, often referred to as the “Achilles’ heel” of hemodialysis patients, represents a significant percentage of the Medicare budget that continues to increase yearly. The purpose of this paper is to review the current literature on the management of vascular access complications and infection treatment and prevention. The paper also explores emerging research regarding the devices and methods to improve access outcomes such as early cannulation arteriovenous grafts, endovascular arteriovenous fistula creation, and regenerative grafts with resorbable scaffolds, among others. The data were collected through literature searches via PubMed, Athens and web search engines.